Proapoptotic and Antiapoptotic Proteins of the Bcl-2 Family Regulate Sensitivity of Pancreatic Cancer Cells Toward Gemcitabine and T-Cell–mediated Cytotoxicity. Issue 3 (April 2015) - Bauer, Christian; Hees, Claudia; Sterzik, Alexander; Bauernfeind, Franz; Mak'Anyengo, Rachel; Duewell, Peter; Lehr, Hans-Anton; Noessner, Elfriede; Wank, Rudolf; Trauzold, Anna; Endres, Stefan; Dauer, Marc; et al.
Abstract : Sensitivity of carcinoma cells towards gemcitabine (Gem) has been linked to mitochondrial apoptotic proteins. Recently, we described synergistic efficacy of Gem-based chemoimmunotherapy and a dendritic cell (DC) tumor vaccine in a murine pancreatic carcinoma model. Here, we investigated the role of the mitochondrial proteins Bcl-2, Bcl-xL, and Bax for sensitization of pancreatic carcinoma cells toward T-cell–mediated cytotoxicity alone and in combination with Gem. Bcl-2 expression was silenced by siRNA in Panc02 pancreatic cancer cells expressing the model antigen ovalbumin (PancOVA). Tumor cells were treated with Gem and/or siRNA, and cytotoxicity induced by OVA-specific cytotoxic T lymphocytes (CTL) from OT-1 mice was assessed. Gem-induced and T-cell–induced cytotoxicity was also studied in human Colo357 pancreatic cancer cell lines overexpressing Bax or Bcl-xL. Apoptosis induction by Fas-activating antibody was measured by Annexin V staining. The in vivo capacity of Bcl-2 siRNA to augment CTL efficacy induced by DC vaccinations was assessed in C57BL/6 mice bearing PancOVA tumors. PancOVA cells treated with Bcl-2 siRNA were sensitized towards both Gem and T-cell–mediated killing; combination therapy exhibited an additive effect. Bax overexpression sensitized Colo357 cells to both Gem-mediated and T-cell–mediated cytotoxicity, whereas Bcl-xL overexpression was inhibitory. Combining Bcl-2 silencing with DC therapy improved tumor control in the PancOVA model in vivo without affecting the number of tumor-reactive CTL. In conclusion, expression of Bcl-2, Bcl-xL, and Bax in pancreatic tumor cells determines sensitivity towards both Gem-mediated and CTL-mediated toxicity. Bcl-2 silencing could be exploited therapeutically in tumor vaccine approaches.